2021
DOI: 10.7759/cureus.15101
|View full text |Cite
|
Sign up to set email alerts
|

Mind the Localized Skeletal Pain: Chronic Recurrent Multifocal Osteomyelitis

Abstract: Chronic recurrent multifocal osteomyelitis (CRMO) is a rare idiopathic aseptic inflammatory bone disorder affecting primarily children and adolescents characterized by an insidious onset of pain, swelling, and tenderness over the affected bones. The clinical signs and symptoms of CRMO are nonspecific, radiological and histopathological tests are essential for its diagnosis.We present a case of an 18-year-old young man who was diagnosed with CRMO by a combination of clinical data, laboratory results, radiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Although CRMO is considered a benign disease with an overall good clinical outcome (36,37) , it has also been shown that severe sequelae may occur (38) . According to the literature, patients with CRMO have up to 50% incidence of residual injury (5) and permanent injury or long-term disability can even occur (4,39) , including multiple fractures, skeletal deformities, and severe growth impairment (40) . Therefore, identifying and diagnosing CRMO as early as possible and treating it appropriately and promptly can improve the quality of life of the affected patients and their families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CRMO is considered a benign disease with an overall good clinical outcome (36,37) , it has also been shown that severe sequelae may occur (38) . According to the literature, patients with CRMO have up to 50% incidence of residual injury (5) and permanent injury or long-term disability can even occur (4,39) , including multiple fractures, skeletal deformities, and severe growth impairment (40) . Therefore, identifying and diagnosing CRMO as early as possible and treating it appropriately and promptly can improve the quality of life of the affected patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic recurrent multifocal osteomyelitis (CRMO), also known as chronic nonbacterial osteomyelitis, is an autoin ammatory disease that manifests as recurrent ares of in ammatory bone pain with or without fever (1)(2)(3)(4) . CRMO is an orphan disease with an estimated prevalence of 1-2/1000000 (5) ; however, because the diagnosis of CRMO is challenging and prone to misdiagnosis, the true prevalence of CRMO may be higher (6,7) .…”
Section: Introductionmentioning
confidence: 99%